Efficacy of Pgp3 vaccination for Chlamydia urogenital tract infection depends on its native conformation - Peng, Bo; Zhong, Shufang; Hua, Yaoqin; Luo, Qizheng; Dong, Weilei; Wang, Chuan; Li, Zhongyu; Yang, Chunfen; Lei, Aihua; Lu, Chunxue (Frontiers in Immunology, 2022)
Urogenital tract infections with Chlamydia trachomatis have frequently been detected among patients diagnosed with sexually transmitted infections, and such infections lead to inflammatory complications. Currently, no licensed chlamydial vaccine is available in clinical practice. We previously reported that immunization with recombinant C. trachomatis plasmid-encoded virulence factor Pgp3 provided cross-serovar protection against C. muridarum genital tract infection. Because Pgp3 is a homotrimer and human antisera only recognize the trimeric form of Pgp3, we compared the effects of the native conformation of Pgp3 (trimer) and heat-denatured Pgp3 (monomer) to determine whether the native conformation is dispensable for the induction of protective immunity against chlamydial vaginal challenge. Both Pgp3 trimer and monomer immunization induced corresponding specific antibody production, but only trimer-induced antibody recognized endogenous Pgp3, and trimer-immunized mouse splenocytes showed the highest IFN-γ production upon restimulation with the chlamydial elementary body or native Pgp3 in vitro. Importantly, only Pgp3 trimer-immunized mice showed shortened lower genital tract chlamydial shedding and decreased upper genital tract pathology. Thus, Pgp3-induced protective immunity against Chlamydia urogenital tract infection is highly dependent on the native conformation, which will guide the design of Pgp3-based polypeptides and multi-subunit chlamydial vaccines.